Exploration of the Pathogenesis of Hp-associated Chronic Atrophic Gastritis in Association with the Theory of Latent Damp-heat - Zhang, Yanzhao; Xu, Yongpan (Journal of Contemporary Medical Practice, 2024)
The incidence of Helicobacter pylori infection in China is relatively high, and Helicobacter pylori can mediate the development of normal gastric mucosa to chronic atrophic gastritis, while chronic atrophic gastritis can develop into precancerous changes such as intestinal metaplasia over a long period of time, ultimately leading to gastric cancer. The nature of Helicobacter pylori is similar to that of the latent damp-heat of Traditional Chinese Medicine (TCM). Therefore, this paper discusses the occurrence and development mechanism of chronic atrophic gastritis associated with Helicobacter pylori, and introduces in detail the pathogenesis of chronic atrophic gastritis caused by the theory of latent damp-heat in Chinese medicine, discusses the relationship between H. pylori, chronic atrophic gastritis and latent damp-heat and provides a new treatment for chronic atrophic gastritis based on the theory of "latent damp-heat". It also discusses the relationship between Helicobacter pylori and latent damp-heat, and provides a new treatment idea for chronic atrophic gastritis from the theory of "latent damp-heat".